Critical Success Factors (CSFs) of Balanced Scorecard Implementation in Public Sector Institution (A Study in the Ministry of Foreign Affairs (MoFA) Indonesia) - Sirait, Bernard Teguh Rizaldi; Wijaya, Andy Fefta; Putra, Fadillah (Jurnal Ilmiah Administrasi Publik, 2020)
Implementing Balanced Scorecard (BSC) in public sector’s performance management system is interesting, due to public sector’s concern for performance measurement. As one promising performance management tools, BSC was originally designed for the private sector institution, but later gaining its popularity among the public institutions. How well BSC implementation is possibly determined by some Critical Success Factors (CSFs). This study examined some CSFs in the BSC implementation in the Ministry of Foreign Affairs (MoFA) Indonesia using a qualitative study with an interactive model by Miles at al., (2014). This study found that BSC implementation brought changes in the MoFA’s performance, despite the absence of organizational changes for BSC adaptation. Top and middle management attention for the implementation and training and education are the most determining factors in the BSC implementation in MoFA. This study support the importance of the four CSFs examined in this study in implementing BSC in public sector.